BcMettl4-Mediated DNA Adenine N6-Methylation Is Critical for Virulence of Botrytis cinerea - Miao, Zhengang; Wang, Guangyuan; Shen, Heng; Wang, Xue; Gabriel, Dean W.; Liang, Wenxing (Frontiers in Microbiology, 2022)
DNA adenine N6-methylation (6mA) plays a critical role in various biological functions, but its occurrence and functions in filamentous plant pathogens are largely unexplored. Botrytis cinerea is an important pathogenic fungus worldwide. A systematic analysis of 6mA in B. cinerea was performed in this study, revealing that 6mA is widely distributed in the genome of this fungus. The 2 kb regions flanking many genes, particularly the upstream promoter regions, were susceptible to methylation. The role of BcMettl4, a 6mA methyltransferase, in the virulence of B. cinerea was investigated. BcMETTL4 disruption and point mutations of its catalytic motif “DPPW” both resulted in significant 6mA reduction in the genomic DNA and in reduced virulence of B. cinerea. RNA-Seq analysis revealed a total of 13 downregulated genes in the disruption mutant ΔBcMettl4 in which methylation occurred at the promoter sites. These were involved in oxidoreduction, secretory pathways, autophagy and carbohydrate metabolism. Two of these genes, BcFDH and BcMFS2, were independently disrupted. Knockout of BcFDH led to reduced sclerotium formation, while disruption of BcMFS2 resulted in dramatically decreased conidium formation and pathogenicity. These observations indicated that 6mA provides potential epigenetic markers in B. cinerea and that BcMettl4 regulates virulence in this important plant pathogen.